1270. HIV Drug Resistance and Viral Outcomes after 2nd-line Antiretroviral Failure in Kenya. (15th December 2022) - Ali, Shamim M; Humphrey, John; Novitsky, Vladimir; Sang, Edwin; DeLong, Allison; Jawed, Bilal; Kemboi, Emmanuel; Goodrich, Suzanne; Gardner, Adrian; Hogan, Joseph W; Kantor, Rami
Abstract: Background: Program data on HIV drug resistance and clinical outcomes after 2nd-line antiretroviral therapy (ART) failure in resource-limited settings are limited, yet can inform care, particularly with better ART access and options. Methods: We examined resistance upon 2nd-line failure and subsequent viral outcomes at the Academic Model Providing Access to Healthcare (AMPATH) in Kenya. Charts of people with genotypes upon 2nd-line failure up to 6/2021 were reviewed; and associations with viral suppression (< 1000 copies/mL) closest to 12 months post-genotyping were determined using bi- and multivariate analyses, adjusting for age, sex, time on ART, switch to 3rd-line (darunavir-, dolutegravir-, and/or raltegravir-based ART), and any resistance to regimens upon viral load (VL) testing. Results: Of 194 participants (53% female; median age 41 years; median 3.3 and 4.1 years on 1st- and 2nd-line), 60% were on lopinavir/ritonavir and 40% on atazanavir/ritonavir-based regimens. Overall, 178 (92%) had any resistance: 19% mono-, 40% dual-, 41% triple-class; 79% to NRTIs; 81% NNRTIs; and 43% PIs - 33% of those on lopinavir/ritonavir; 58% on atazanavir/ritonavir (p< 0.001); 24% with intermediate-high predicted resistance to darunavir/ritonavir (12 upon LPV/ritonavir, and 8 upon atazanavir/ritonavir failure; p=0.98). Of 140/194 people with post-genotype VLs, 55% stayed on 2nd-line, and 45% switched to 3rd-line. Of those 140, 72% virally suppressed (89% who switched to 3rd-line; 58% who didn't), and 75% had any resistance to their regimen at post-genotype VL (90% who switched to 3rd-line; 62% who didn't). In bivariate analysis, suppression was associated with switching to 3rd-line, and with resistance upon VL testing (Table). In multivariate analysis, suppression remained more likely among those who switched to 3rd-line, and association with resistance was less pronounced. Conclusion: In a large Kenyan HIV program, high resistance upon 2nd-line failure, high failure rates, and suppression association with 3rd-line switch suggest the need for dedicated management of this vulnerable population. Potential association between resistance and better viral outcomes, similar to reports upon 1st-line failure, needs further data and suggests significance of inadequate adherence. Disclosures: All Authors : No reported disclosures.